Practical challenges and Obligations for conducting Clinical Trial in Nepal: A call for improvement - Ibnas, Muhamed; Asim, Mohammad; Mekkodathil, Ahammed; Sathian, Brijesh (Nepal Journal of Epidemiology, 2019)
Clinical trials play a central role in human subject research for the betterment of health care outcomes. Clinical trials are based on experimental research design in which human subjects are being enrolled in a study arm to assess the safety and efficacy of an investigational product in a protocolized manner.